2010
DOI: 10.18097/pbmc20105603372
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of oxide-dependent and nitroxide-forming enzymatic systems of macrophages under staphylococcus aureus and listeria monocytogenes infections

Abstract: Впервые в сравнительном аспекте показана реактивность кислородзависимой и нитроксидобразующей ферментных систем макрофагов при заражении бактериями, различающимися по механизмам фагоцитоза: с внутрифагосомальной (Staphylococcus aureus) и внутрицитоплазматической (Listeria monocytogenes) локализацией в фагоцитах. Приведены данные о различиях ферментативной активности (сукцинатдегидрогеназа, лактатдегидрогеназа, цитохромоксидаза, NADP-оксидазный комплекс в НСТ-тесте) макрофагов в ответ на заражение указанными ви… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…At examination of bactericidal activity of reactive nitrogen and oxygen species on S. aureus Kaplan and co-authors showed, what exactly the combined action of NO and O 2 -results in prolonged, but complete destruction of S. aureus, whereas separate influence of these molecules is transient and ineffective 21 . Predominance of one of the mentioned bactericidal systems depending on both a type and degree of pathogen virulence is also described 19 . Apparently, only at maintenance of optimal balance between the levels of ROS and NO production and antigen influence the adequate realization of phagocyte bactericidal action is possible.…”
Section: Discussionmentioning
confidence: 99%
“…At examination of bactericidal activity of reactive nitrogen and oxygen species on S. aureus Kaplan and co-authors showed, what exactly the combined action of NO and O 2 -results in prolonged, but complete destruction of S. aureus, whereas separate influence of these molecules is transient and ineffective 21 . Predominance of one of the mentioned bactericidal systems depending on both a type and degree of pathogen virulence is also described 19 . Apparently, only at maintenance of optimal balance between the levels of ROS and NO production and antigen influence the adequate realization of phagocyte bactericidal action is possible.…”
Section: Discussionmentioning
confidence: 99%